2022
DOI: 10.1186/s12893-022-01522-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for chronic postsurgical pain following video-assisted thoracoscopic surgery: a retrospective study

Abstract: Background Video-assisted thoracoscopic surgery (VATS) has been widely used as an alternative for thoracotomy, but the reported incidence of chronic postsurgical pain (CPSP) following VATS varied widely. The purpose of this study was to investigate the incidence and risk factors for CPSP after VATS. Methods We retrospectively collected preoperative demographic, anesthesiology, and surgical factors in a cohort of patients undergoing VATS between Jan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 34 publications
1
26
1
Order By: Relevance
“…Thereafter, 183 records were carefully reviewed to ensure compliance with the inclusion criteria. Ultimately, 17 studies [10][11][12][20][21][22][23][24][25][26][27][28][29][30][31][32][33], comprising 10,525 patients who underwent VATS, were included in this study (Fig. 1).…”
Section: Included Studiesmentioning
confidence: 99%
“…Thereafter, 183 records were carefully reviewed to ensure compliance with the inclusion criteria. Ultimately, 17 studies [10][11][12][20][21][22][23][24][25][26][27][28][29][30][31][32][33], comprising 10,525 patients who underwent VATS, were included in this study (Fig. 1).…”
Section: Included Studiesmentioning
confidence: 99%
“…It has been reported to occur in 15% (365/2,396) in one case series and 44% (1,033/2,348) in another with 6.5% (152/2,348) in the moderate to severe range. 55 56…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…Nonetheless, the highest incidence of CPSP can still reach 37.4% with a VATS lobectomy ( 12 ). The occurrence of CPSP causes a severe disturbance in patients’ emotional state and sleep quality, leading to a number of psychological issues that immensely impact their prognosis and quality of life ( 9 , 13 , 14 ). Hence, identifying the predictive factors associated with CPSP after VATS will help clinicians achieve targeted prevention and treatment to support patients in re-establishing confidence and improving their quality of life ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of retrospective studies have investigated the associated risk factors for the development of CPSP after VATS, including body mass index (BMI), history of pain, and acute postoperative pain ( 13 , 14 , 16 19 ). Further, studies have indicated that microRNAs (miRNAs) in the peripheral blood of patients with chronic neuropathic pain are closely associated with chronic neuropathic pain ( 20 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation